(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
In this article, the categories of quantity in Uzbek, English and Russian languages are nationally modeled. In this process, the models of quantitative categories in different languages are analyzed linguistically. It is argued that the grammatical category of noun is preserved in the minds of members of society as universality, invariance, essence, possibility, and the grammatical forms characteristic of them are reflected in reality as various speech options and events. Also, grammatical categories are recognized as paradigms, in turn, on the example of affix models, it is explained that the grammatical forms included in this paradigm are preserved in the minds of native speakers as universality.